Lapatinib Suppresses HER2-Overexpressed Cholangiocarcinoma and Overcomes ABCB1– Mediated Gemcitabine Chemoresistance - Bai, Zhiqing; Guo, Zhiying; Liu, Jiaxing; Chen, Yu-Ann; Lu, Qian; Zhang, Ping; Hong, Lili; Wang, Yunfang; Dong, Jiahong (Frontiers in Oncology, 2022)
Background: Recent breakthroughs in cholangiocarcinoma (CCA) genomics have led to the discovery of many unique identifying mutations, of which HER2 has been found to be overexpressed specifically in cases of extrahepatic CCA. However, whether or not lapatinib (an oral tyrosine kinase inhibitor selective for inhibition of HER2), or a combination of lapatinib and gemcitabine, exerts inhibitory effects on HER2-overexpressed CCA is still unclear. Methods: Histopathological characterization and HER2 status of CCA organoids were assessed by multiplex immunofluorescence. The effect of lapatinib and a lapatinib-gemcitabine combination treatment on CCA was determined using organoid and cell line models. Cell cycle arrest, apoptosis and proteins involving HER2-dependent downstream signaling pathways were analyzed to assess the effect of lapatinib on HER2+ CCA. The synergistic effect of lapatinib and gemcitabine was interpreted by docking analysis, ABCB1-associated ATPase assay, rhodamine transport assay and LC-MS/MS analyses. Results: HER2 status was found to be well maintained in patient-derived CCA organoids. Lapatinib exerts a dual effect on HER2-overexpressed CCA, suppressing the growth of CCA cells by inhibiting HER2 and HER2-dependent downstream signaling pathways while inhibiting ABCB1 transporter function, allowing for the accumulation of active chemotherapy metabolites within cells. Conclusions: Our data demonstrates that lapatinib can not only inhibit growth of CCA overexpressing HER2, but can also circumvent ABCB1-mediated chemoresistance after gemcitabine treatment. As such, this provides a preclinical rationale basis for further clinical investigation into the effectiveness of a combination treatment of lapatinib with gemcitabine.